Managing the Risks of the Automobile: A Study of a Swedish Car Manufacturer - Svenson, Ola (Management Science, 1984)
Hazard management of the risks of human injury and death related to the automobile are described and exemplified by the Swedish car manufacturer Volvo. The study presents the Volvo units engaged in accident hazard management and their roles in the elaborate system of feedbacks (information, penalties and rewards) created by the company and society for maintaining a high level of automobile safety. Improvements are suggested although the overall quality of the accident hazard management process is considered quite good. Although the study is focused on the automobile industry, it should be regarded as part of a much-needed wider perspective on hazard management applying to other technologies and industries as well. In general, the following factors are considered important to high quality accident hazard management by companies and society: (1) Public concern about safety issues, (2) technological capacity and organizational tradition of safety engineering in the manufacturing company, (3) routines for announcing future proposed safety standards, e.g., US Federal Register, (4) laws enforcing a recall system, (5) annual vehicle inspections and (6) effective product liability laws.